Cyclotosaurus naraserluki, sp. nov., a new Late Triassic cyclotosaurid (Amphibia, Temnospondyli) from the Fleming Fjord Formation of the Jameson Land Basin (East Greenland) - Marzola, Marco (2017)
Sem PDF. Fundacao para a Ciencia e a Tecnologia (SFRH/BD/99580/2014) European Association of Vertebrate Palaeontologists Research Grant (EAVP-ERG) Stan Wood Award of The Palaeontological Association (PA-SW201502) Carlsberg Foundation